THE ADMISSIBILITY OF ELECTRONIC EVIDENCE IN RELATION TO THE RIGHT TO PRIVACY IN CASES OF SEXUAL CONTENT DISSEMINATION - Safaruddin Harefa (Faculty of Law Atma Jaya Yogyakarta University, 2026)
The rapid advancement of digital technology has transformed the nature of crime and evidence, requiring legal systems to accommodate electronic forms of proof. This study analyzes the admissibility of electronic evidence in Indonesian criminal procedure law and its implications for the protection of privacy, particularly in cases involving the dissemination of sexual content. Using a normative juridical approach, this research examines statutory frameworks, including the ITE Law and its 2024 amendment, the 1945 Constitution, Law No. 20 of 2025 on the new Criminal Procedure Code, and Law No. 27 of 2022 on Personal Data Protection. It also employs a case study of the Pandeglang District Court Decision No. 71/Pid.Sus/2023/PN Pdl to assess the gap between das sollen and das sein. The findings indicate that Indonesia has normatively established a clear legal basis recognizing electronic evidence as valid and binding. However, judicial practice, particularly in cases decided prior to the enactment of the new KUHAP and the Personal Data Protection Law, tends to prioritize evidentiary validity over the protection of victims’ privacy. The Pandeglang case demonstrates that although electronic evidence was lawfully admitted, the absence of procedural safeguards created risks of re-victimization and undermined the victim’s dignity. This study concludes that while the issue of admissibility has been resolved under the current legal framework, challenges remain in ensuring privacy protection in judicial practice. Therefore, courts must adopt rights-sensitive approaches, including closed hearings, anonymization, and proportional use of evidence, to balance evidentiary effectiveness with the protection of fundamental rights in the digital era.